Photoluminescence properties of carbon nanoparticles synthesized from activated carbon powder (4% ash) by laser ablation in solution. (July 2017) - Yogesh, Gaurav Kumar; Shuaib, E.P.; Sastikumar, D.
Graphical abstract: Highlights: Synthesis of CNPs from activated carbon (4% ash) by laser ablation in solutions. CNPs exhibit amorphous and crystalline type structures. Green and blue emissions are obtained under UV light. Abstract: Carbon nanoparticles (CNPs) were prepared by laser ablation of activated carbon (4% ash) in water + ethanol solution (5:2 by volume). Average particle size of about 14 nm was observed and CNPs exhibited a crystalline structure. When 2 mL of NaOH (0.185 M) was added to water + ethanol solution, the average particle size was about 4 nm and the amorphous structure was observed. Photoluminescence (PL) of synthesized CNPs in the absence of NaOH showed spectral peak intensity in the blue region (466 nm) whereas it shifted to the green region (515 nm) for CNPs synthesized with NaOH. The PL of both CNPs exhibited excitation dependent. FWHM of PL spectra of CNPs decreased with increase in the excitation wavelength for a solution without NaOH whereas it increased initially and then decreased for CNPs synthesized with NaOH.